Exploring the Impact of an Innovative Peer Role-Play Simulation to Cultivate Student Pharmacists' Motivational Interviewing Skills - Paul Denvir; Laurie L. Briceland (MDPI AG, 2023)
Effective patient-centered communication is a foundational skill for student pharmacists, with recent decades broadening the scope of professional responsibilities to include an increased emphasis on empathic communication and motivational interviewing (MI) as tools to support patients' therapeutic adherence. Role-play is a potentially effective pedagogical approach to cultivate these skills, although previous research has identified common shortcomings that can hinder its educational value, particularly in peer role-play with relatively inexperienced learners. The purpose of this study is to describe and provide initial assessment data for an innovative approach to peer role-play that incorporates pedagogical principles to address these common shortcomings. Using a mixed-methods study design that includes instructor-graded rubrics and inductive thematic analysis of student reflections, our findings indicate that students successfully demonstrated a range of important competencies through this experience and perceived it to be both challenging and highly beneficial for their personal and professional development. Among the MI principles and techniques practiced, students performed especially well on expressing empathy and frequently reflected on its importance for future patient care and clinical collaborations. Our findings also suggest that peer engagement through team activities and partnered role-play provides a felicitous context to explore empathic communication together.